Fog water traps as a low-cost alternative source of wáter in coastal desert areas of the Pacific: Trampas de agua de niebla como fuente alternativa de agua de bajo costo en zonas desérticas costeras del Pacífico - Morales Vergara, Luis P; Cunha Lima, Ricardo; Bonnail, Estefanía; González Allende, Carlos (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2023)
Water scarcity is the most common concept associated with the desert. The Atacama Desert is worldly known as the aridest desert on Earth. However, some populations are established in this area, requiring water for living that promotes the search of alternative water sources, as fog catchers taking in advance the regional fog event known as Camanchaca. During 2015, the construction of fog trap units was carried out on a hill in the Falda Verde sector in Chañaral (North Chile). In the design of these new fog trap units it was considered to improve the anchoring system and the distribution and angles of the clamping tensioners in order that the structure could withstand the maximum wind speeds that have been registered in the area, while recording the water accumulated by these units during a period of 12 months determined an average catchment of 22 liters of water/m2 per month.